2006
DOI: 10.1007/s11103-005-2763-4
|View full text |Cite
|
Sign up to set email alerts
|

Something on the Side: Axillary Meristems and Plant Development

Abstract: Axillary meristems allow the production of secondary growth axes in the shoot systems of plants. As such they make a large contribution to the plastic developmental potential of plants, allowing them to alter their architecture to suit the prevailing environment conditions. This review focuses on the formation and activity of axillary meristems, across several model species. Current topics and problems in the field are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 65 publications
2
80
0
1
Order By: Relevance
“…Many genes have been identified that regulate axillary meristem initiation and outgrowth during vegetative and reproductive development (Schmitz and Theres, 2005;Bennett and Leyser, 2006;Doust 2007b). Most of these genes have been identified as mutants that have fewer branches, because axillary meristems fail to initiate, or that are bushier than normal due to constitutive outgrowth of axillary buds.…”
mentioning
confidence: 99%
“…Many genes have been identified that regulate axillary meristem initiation and outgrowth during vegetative and reproductive development (Schmitz and Theres, 2005;Bennett and Leyser, 2006;Doust 2007b). Most of these genes have been identified as mutants that have fewer branches, because axillary meristems fail to initiate, or that are bushier than normal due to constitutive outgrowth of axillary buds.…”
mentioning
confidence: 99%
“…Several genes promoting axillary bud initiation have been identified in different model species (Bennett and Leyser 2006;Kebrom et al 2013) and their supposed functions could be confirmed by transgenic approaches. For instance, a transcription factor of the GRAS family characterized in tomato, rice and Arabidopsis, -Lateral suppressor (Ls), Monoculm1 (MOC1) and LATERAL SUPPRESSOR (LAS), respectively -is responsible for the establishment of an axil identity and maintenance of meristematic capacity via prevention of cell de-differentiation (Bennett and Leyser 2006;Greb et al 2003;Li et al 2003a;Schmitz and Theres 2005;Ward and Leyser 2004).…”
Section: Vegetative Propagationmentioning
confidence: 98%
“…The time of formation of axillary meristems can be determined by the developmental stage of the plant (Grbić and Bleecker 2000), although this can vary according to the species. While in tomato all axillary meristems seem to appear immediately in the leaf axil when the leaf is formed, in Arabidopsis they do not all form at the same time and some leaf axils never form an axillary meristem (Bennett and Leyser 2006). In any case, the axil identity where the future axillary meristem will form needs to be established first.…”
Section: What Is Known About Axillary Meristem Formation and Outgrowtmentioning
confidence: 98%
See 2 more Smart Citations